Dyskryminacja kobiet w sferze bezrobocia w Polsce w latach 2000-2006 - Natalli, Krzysztof; Szczepanik, Maciej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main purpose of the paper is to analyze an unemployment of women and men in the Polish labour market between 2000 and 2006. It should allow to verify if there existed a discrimination against women connected with unemployment. It is also important to check the level of discrimination and how it changed during this period of time. The discrimination connected with unemployment will be treated as a situation, when women - in spite of having comparable social, professional, and demographical features - become unemployed more often, for longer time and have bigger problems to find a new job than men. That means that women are discriminated only because of the sex, despite the same job efficiency, level of education, job seniority, experience, and abilities. It seems to be very interesting how the discrimination against women changed during the years 2000-2006. In these years it can be observed that Polish government put a big pressure on equal rights for women and extended the protection of women employment according to the process of adapting the Polish law to the law of the European Union. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 363-376